Assessment of Genotoxicity through ISSR Marker in Pistia stratiotes Induced by Lead - Lamyai Neeratanaphan; Runglawan Sudmoon; Arunrat Chaveerach (EnvironmentAsia, 2014)
Assessment of DNA changes in Pistia stratiotes induced by lead (Pb), plants were grown in acclimatized conditions for 15 days. Each of 5 plants were then transferred to cultivate in three repeated 0.2, 0.3, 0.5 mg/l Pb experiments, four days and controls. Lead concentration in water was analyzed by inductively-coupled plasma - mass spectrometry (ICP-MS), physical and chemical factors including temperature, pH, dissolved oxygen (DO) and electro-conductivity (EC) before and after the experimentation. Inter-simple sequence repeat fingerprints (ISSR) were analyzed for genetic similarity values (S), and genomic template stability test (GTS) was evaluated for revealing correlation of genetic structure changes and induced Pb concentration levels. The results appeared that the mean Pb concentrations in water were decreased 0.0121, 0.1688 and 0.2338 mg/l in the 3 concentration experiments, respectively. Assumedly, these Pb values loosed were adsorbed and absorbed in the plants. The physical and chemical factors such as pH, DO and EC were decreased and temperature was increased. The 10 successfully ISSR primers produced a total of 577 bands used for dendrogram construction. The plants with Pb affected 0.2, 0.3 and 0.5 mg/l were correlated by each concentration grouping and the S reveals 0.85-0.90, 0.69-0.90 and 0.93-0.96, respectively. The S value and plant's individual grouping agreement reveal its true effect by each Pb concentration. GTS values were (-2.38) - (-23.81) signifying to have most changes in DNA structure, genetic erosion occurring thoroughly on its genome, and affecting its life. These effects agreed to its morphological characters including leaves lacking chlorophyll (yellow), beginning to decay and finally dying. The research shows that P. stratiotes can be used as a bio-indicator for Pb wastewater monitoring.